Cultural competence questionnaire for help professionals (CCQ-HP): Transcultural translation and factorial validation - Gonçalves, Mariana (2019)
Objective: to adapt and validate the Cultural Competence Assessment Instrument designed to measure the cultural competence of help professionals. The questionnaire was selected according three criteria: i) the construction process of the same in its original version, based on a thorough review of the existing literature and available instruments to evaluate the construct; ii) adjustment indicators of validation of the model; iii) the adequacy and the ability to adapt to the pretended contexts, particularly among help professionals.Method: the translation and adaptation of the questionnaire obey to international guidelines in this area and validation was conducted with 313 help professionals from three professional areas: social, health and criminal.Results: Exploratory and confirmatory factor analysis allowed to identify for this sample, with good psychometric adjustment (e.g., alpha .88), the cultural competence measured by four factors: cultural awareness, cultural knowledge, technical skills and organizational support.Conclusions: The Portuguese version of the assessment instrument of cultural competence is a smaller version of the original instrument, which can be used in different areas. This instrument is therefore useful in monitoring and supervising institutional practices in care in help contexts, at the level of cultural competence.